2022
DOI: 10.1152/ajpheart.00574.2021
|View full text |Cite
|
Sign up to set email alerts
|

Aortic stiffness is lower when PVAT is included: a novel ex vivo mechanics study

Abstract: Perivascular adipose tissue (PVAT) is increasingly recognized as an essential layer of the functional vasculature, being responsible for producing vasoactive substances and assisting arterial stress relaxation. Here we test the hypothesis that PVAT reduces aortic stiffness. Our model was the thoracic aorta of the male Sprague Dawley rat. Uniaxial mechanical tests for three groups of tissue were performed: aorta +PVAT (+PVAT), aorta - PVAT (-PVAT), and isolated PVAT (PVAT only). The output of the mechanical tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Second, our functional studies only evaluated vascular responses to adrenergic stimulation, which means that endothelial function was not directly assessed. Third, the contributions of PVAT to arterial stiffness were disregarded in this study, but recent evidence shows that vessel stiffness is lower when PVAT is present [ 18 ]. Notwithstanding these limitations, we firmly believe that our work narrows a fundamental knowledge gap: how sex as a variable affects intrinsic media-layer stiffness in young animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, our functional studies only evaluated vascular responses to adrenergic stimulation, which means that endothelial function was not directly assessed. Third, the contributions of PVAT to arterial stiffness were disregarded in this study, but recent evidence shows that vessel stiffness is lower when PVAT is present [ 18 ]. Notwithstanding these limitations, we firmly believe that our work narrows a fundamental knowledge gap: how sex as a variable affects intrinsic media-layer stiffness in young animals.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, 2 mm endothelium-intact rings were obtained from the thoracic aorta, and mounted with a physiological preload of 15 mN/mm. Since PVAT modifies aortic stiffness [ 18 ], studies were conducted in PVAT-denuded vessels. Each myograph chamber was filled with physiological salt solution (PSS; mmol/L: 130 NaCl, 4.7 KCl, 1.18 KH 2 PO 4 , 1.18 MgSO 4 * 7H 2 O, 14.9 NaHCO 3 , 5.6 Dextrose, 1.56 CaCl 2 * H 2 O, 0.026 EDTA), which was gassed with carbogen (95% CO 2 / 5% O 2 , pH: 7.4) and kept at 37 C. Samples were allowed to equilibrate for approximately 1 h. To test for the viability of the rings, we used a high K + solution (120 mmol/L for 10 min) modified from PSS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, another intriguing and largely unexplored research question is the precise role of perivascular adipose tissue (PVAT) in vascular health and diseases, such as atherosclerosis ( 45 , 47 ). Recent evidence has implicated PVAT as the fourth layer of the blood vessel wall (the tunica adiposa), which produces adipokines and vasoactive substances (such as leptin, adiponectin, resistin, and visfatin)/cytokines/growth factors that regulate vascular tone/homeostasis ( 4 , 48 ). One study from Tang laboratory have revealed that periaortic knockdown of ribosomal protein S3A (RPS3A) in mouse PVAT impaired PVAT browning, promoted vascular inflammation and atherosclerosis development by modulating UCP-1 expression in ApoE -/- mice ( 49 ).…”
Section: Vascular Wall Components In Vascular Homeostasis and Atheros...mentioning
confidence: 99%
“…These findings uncover the important role of PVAT in regulating endothelial function, inflammation and atherosclerosis. Future studies including PVAT in measuring aortic wall’s mechanical behavior, such as aortic stiffness and vasorelaxation/constriction is important ( 48 ).…”
Section: Vascular Wall Components In Vascular Homeostasis and Atheros...mentioning
confidence: 99%